Individual Features in the Contemporary Polish Reportage: A Syntactic and Stylistic Study on the Basis of "Zabójca z miasta moreli: reportaże z Turcji" by Witold Szabłowski - Katarzyna Małgorzata Ostrowska (Półrocznik Językoznawczy Tertium, 2020)
The article deals with the language individual features in the contemporary Polish reportage based on the text Zabójca z miasta moreli: reportaże z Turcji by Witold Szabłowski. The author presents both the statistical analysis and the stylistic peculiarities of this reportage which was prized a prestigious Beata Pawlak Award in 2011 and contains important components characteristic for the journalistic style. The author uses the traditional syntactic model of Zenon Klemensiewicz and takes into consideration Stanisław Jodłowski’s research achievements. According to the postulates of Anna Wierzbicka, Maria Rachwałowa, Stanisław Mikołajczak, and Marek Ruszkowski, she selects a sample of 200 utterances which are examples of such narrative constructions that strongly indicate subjectiveness. In her research, firstly, she conducts a detailed analysis of the syntactic and statistical features of Szabłowski's text in comparison with the style of the contemporary Polish reportage. Secondly, she draws attention to stylistic unique features indicating the reporting syntax. As a result, the author notices the following language individual features in Zabójca z miasta moreli: reportaże z Turcji by Witold Szabłowski: 1) simple utterances and direct and indirect objects in the developed sentences, 2) developed clauses and adverbials, 3) objective hypotaxis, and 4) adverbial hypotaxis.